Case Report: Homozygous DNAJC3 Mutation Causes Monogenic Diabetes Mellitus Associated With Pancreatic Atrophy - Alwatban, Saud; Alfaraidi, Haifa; Alosaimi, Abdulaziz; Alluhaydan, Iram; Alfadhel, Majid; Polak, Michel; Almutair, Angham (Frontiers in Endocrinology, 2021)
Introduction: DNAJC3, which is abundant in the pancreatic cells, attenuates endoplasmic reticulum stress. Novel homozygous DNAJC3 mutations have been reported to cause non-immune juvenile-onset diabetes, neurodegeneration, hearing loss, short stature, and hypothyroidism. Case description: We report a case of homozygous DNAJC3 mutation in two siblings of a consanguineous family. A 3-year-old boy presented with short stature and a thyroid nodule. Laboratory findings confirmed hypothyroidism. Subsequently, levothyroxine was administered. Growth hormone (GH) stimulation test results were within the normal limits. His stature was exceedingly short (80.5 cm) (<1st percentile, −3.79 SD). The patient developed sensorineural hearing loss at age 6 years. His intellectual functioning was impaired. GH treatment was postponed until the age of 6 years due to a strong family history of diabetes. At age 9 years, he developed an ataxic gait. Brain magnetic resonance imaging (MRI) revealed neurodegeneration. The patient developed diabetes at the age of 11 years—5 years after the initiation of GH treatment. Tests for markers of autoimmune diabetes were negative. Lifestyle modification was introduced, but insulin therapy was eventually required. Whole exome sequencing revealed a homozygous DNAJC3 mutation, which explained his clinical presentation. MRI revealed a small, atrophic pancreas. At the age of 17 years, his final adult height was 141 cm (Z-score, −5.87). His elder brother, who had the same mutation, had a similar history, except that he had milder ataxia and normal brain MRI finding at the age of 28 years. Conclusion: We propose that DNAJC3 mutation can be considered as a cause of maturity onset diabetes of the young. Patients with DNAJC3 mutations may possess a small atrophic pancreas.